MODEL PEMBELAJARAN PENDIDIKAN AGAMA ISLAM DI SEKOLAH MENENGAH ATAS - Ratna Kasni Yuniendel; Zulvia Trinova (Tarbiyah Islamiyah: Jurnal Ilmiah Pendidikan Agama Islam, 2021)
Abstract: This study aims to describe the learning model of Islamic Religious Education in Senior High Schools. The need for this model starts from the still weak learning of Islamic Religious Education in secondary schools with the majority of students undergoing the adolescent phase. As a result, various negative behaviors such as mass fights, promiscuity, selfishness and lack of concern for values and norms are still attached to students. Psychologically, individuals who are in their teens are in an unstable and sensitive condition. While the implementation of Islamic Religious Education in schools often pays less attention to aspects of the psychological development of students. As a result, the education carried out has less impact on the awareness of students to practice their religious teachings properly. Therefore, Islamic Religious Education based on an understanding of individual students is an alternative model to overcome weaknesses in learning Islamic religious education in high school.Keywords: Islamic education; Learning model; Senior High Schoo Abstrak: Penelitian ini bertujuan untuk mendeskripsikan model pembelajaran Pendidikan Agama Islam di Sekolah Menengah Atas. Perlunya model ini bertitik tolak dari masih lemahnya pembelajaran Pendidikan Agama Islam di sekolah menengah dengan mayoritas peserta didik yang sedang menjalani fase remaja. Akibatnya berbagai perilaku negatif seperti perkelahian masal, pergaulan bebas, egois dan kurang memperdulikan nilai-nilai dan norma masih melekat pada peserta didik. Secara psikologis individu yang menginjak usia remaja berada dalam kondisi yang labil dan sensitif. Sementara pelaksanaan Pendidikan Agama Islam di sekolah seringkali kurang memperhatikan aspek perkembangan psikologis peserta didik. Akibatnya pendidikan yang dilaksanakan kurang berdampak terhadap penyadaran peserta didik mengamalkan ajaran agamanya dengan baik. Oleh karena itu, Pendidikan Agama Islam berbasis pemahaman terhadap individu peserta didik merupakan alternatif model untuk mengatasi kelemahan dalam pembelajaran pendidikan agama Islam di Sekolah Menengah Atas.Kata Kunci: Model Pembelajaran; Pendidikan Agama Islam; Sekolah Menengah Atas